The Effectiveness of 3D Visual Media Based on the Realistic Mathematics Education Approach in Mathematics Learning in Elementary Schools - Masnur; Tatang Herman; Wahyu Naldi (International Conference on Elementary Education, 2023)
3D visual media is media whose appearance can be observed from any point of view and has dimensions of length, width, and height/thickness. There are still many teachers who teach using conventional methods even though there are many contextual media that can be used to deliver learning materials so that students better understand the material being taught. This study aims to determine the effectiveness of a 3D visual media based on the Realistic Mathematics Education approach in grade 5. The method used in this research is experimental research. Data collection is done by determining the population and samples are carried out before the research is carried out. This research was conducted in Class 5C of SD Negeri Cipocok Jaya 1. From the results of the study it can be concluded that the use of 3D visual media can improve student learning outcomes in Class 5C of SD Negeri Cipocok Jaya 1.